ETNOGRAFI SEBAGAI ALAT UKUR IMPLEMENTASI KMA 183 TAHUN 2019 ‎DALAM PEMBELAJARAN AGAMA ISLAM DI MADRASAH - Sutarno Sutarno; Uky Fatanun Fiqih (Tarbiyatuna Kajian Pendidikan Islam, 2022)
Global changes that are so fast trigger various challenges, especially the world of education. Madrasah is an educational institution that emphasizes the religious aspect and does not escape the challenges of education. The implementation of KMA Number 183 in 2019 as a form of response to the implementation of the 2013 curriculum which has a "scientific approach method". The scientific method that has a student-centered character becomes an alternative and a solution so that students are able to have generic competencies and have a high literacy culture and can make religion a pattern of thinking, acting, and acting in everyday life. In measuring this attitude, the ethnographic method is the most appropriate approach. The ethnographic method prioritizes an in-depth data quality so that problems can be known to the root. Keywords: Scientific Learning, Implementation of KMA 183 in 2019, Ethnography‎